Effect of bromine complexing agents on the performance of cation exchange membranes in second-generation vanadium bromide battery - Lim, Tuti Mariana (2015)
The effect of bromine complexing agents, N-ethyl-N-methyl-morpholinium bromide (MEM) and N-ethyl-N-methyl-pyrrolidinium bromide (MEP) on the performance of different perfluorinated cation exchange membranes, ChiNaf and VF11, is assessed in the G2 vanadium bromide battery (V/Br). It is noted that in the absence of MEM and MEP, the thicker ChiNaf (50 μm) membrane shows a higher energy efficiency at a current density of 20 mA cm−2. A preliminary test of ChiNaf at two different concentration ratios of MEM and MEP evaluated at 4 mA cm−2 shows that a mixture of 0.19 m MEM and 0.56 m MEP provides a slightly higher cell efficiency than the other tested compositions. However, better cell performance is obtained with the VF11 (25 μm) membrane at 4 mA cm−2 using 0.19 m MEM and 0.56 m MEP. Further studies using VF11 with a mixture of 0.19 m MEM and 0.56 m MEP at 20 mA cm−2 provide direct evidence that the addition of MEM+MEP lowers the cell performance through a reduction in voltage efficiency. The increased membrane resistance after the introduction of MEM and MEP marks the formation of an organic layer after bromine reacts with MEM and MEP and is deposited onto the membrane.